Pelvic exenterations for gynecologic cancers: A retrospective analysis of a 30-year experience in a cancer center. Issue 12 (December 2018) - Knight, S.; Lambaudie, E.; Sabiani, L.; Mokart, D.; Provansal, M.; Tallet, A.; Houvenaeghel, G.
Abstract: Introduction: The objective of this study was to report a 30-year experience of PE for gynecologic malignancies in a cancer center. Materials and methods: A retrospective study was conducted at Institut Paoli-Calmette including patients who underwent PE for gynecologic malignancies. Four periods were evaluated: P1 before 1992, P2 between 1993 and 1999, P3 between 2000 and 2006 and P4 after 2006. The study evaluated the number of PE performed during each period, the type of PE, its level, indication, location of the primary tumor, patient age, previous radiotherapy ≥45 Gy, the rate of "curative" PE and exenteration-related reconstructive techniques. 90-day post-operative mortality and morbidity using the National Cancer Institute's Common Terminology Criteria for Adverse Events (NCI-CTCAE) v 4.03 were reported. Results: 277 PE were performed. The number of PE performed for recurrences rose during the study period (p = 0.042), PE performed for central tumors increased during P3 (64.4%) and P4 (67.4%) (p < 0.0001) and administration of radiotherapy ≥45 Gy was more frequent (p < 0.0001). The rate of "curative" PE increased (p < 0.0001). In multivariate analysis, "curative" PE were correlated with PE type, central locations and study period. Pelvic filling was progressively more frequently performed (p = 0.002). 90-day complication rate was 56.3%. In multivariate analysis there was a significant difference in distribution of CTCAE grade 3-4-5 morbidity depending on the period. Overall survival (OS) improved during the 2 last periods (p = 0.008). Conclusion: A better selection of eligible patients for PE, namely through improvement in imaging techniques, has enabled to raise the rate of curative PE.